Indigenous Research Methodologies - Chilisa, Bagele (SAGE, 2020)
Author Bagele Chilisa updates her groundbreaking textbook to give a new generation of scholars a crucial foundation in indigenous methods, methodologies, and epistemologies. Addressing the increasing emphasis in the classroom and in the field to sensitize researchers and students to diverse perspectives - especially those of women, minority groups, former colonized societies, indigenous people, historically oppressed communities, and people with disabilities, the second edition of Indigenous Research Methodologies situates research in a larger, historical, cultural, and global context to make visible the specific methodologies that are commensurate with thetransformative paradigm of social science research"
Section: xxiv, 368 pages : illustrations ; 24 cm.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; _Nettoyé